Predicting Anxiety Sensitivity Based on Fatigue and Occupational Stress Among Female Law Enforcement Employees - Rostami, Hossein (Psychology of Woman Journal, 2026)
Objective: The present study aimed to predict anxiety sensitivity based on fatigue and occupational stress among female law enforcement employees in Tabriz.Methods and Materials: This study employed a descriptive-correlational design with a predictive approach. The statistical population consisted of all female law enforcement employees working in Tabriz in 2025. Using convenience sampling, 230 participants were initially recruited, of whom 212 were included in the final analysis after excluding incomplete questionnaires. Data were collected using the Anxiety Sensitivity Index-3, the Multidimensional Fatigue Inventory, and the Health and Safety Executive Occupational Stress Indicator Tool. Data analysis was performed using SPSS version 27 through descriptive statistics, Pearson correlation coefficients, and simultaneous multiple regression analysis.Findings: The results showed that fatigue was positively and significantly correlated with anxiety sensitivity (r = .56, p < .01), and occupational stress was also positively and significantly correlated with anxiety sensitivity (r = .49, p < .01). The findings of multiple regression analysis indicated that fatigue and occupational stress jointly predicted anxiety sensitivity significantly (R = .62, R² = .39, F(2, 209) = 66.08, p < .001). Both fatigue (β = .42, p < .001) and occupational stress (β = .31, p < .001) were significant predictors of anxiety sensitivity, with fatigue showing the stronger predictive contribution.Conclusion: The findings suggest that fatigue and occupational stress are significant predictors of anxiety sensitivity among female law enforcement employees in Tabriz. Higher levels of fatigue and job stress were associated with greater fear of anxiety-related sensations, and fatigue emerged as the stronger predictor. These results highlight the importance of developing organizational and psychological interventions aimed at reducing fatigue, managing occupational stress, and promoting mental health among female law enforcement personnel.